NAVOIY VILOYAT NAVBAHOR TUMANINING TARIXIY MADANIY GEOGRAFIK JIHATLARI - Axmedova, Yu.Q.; Saydillayev, S.O. (SCIENCE and SOCIETY, 2025)
The article shows the history of Navbahor, geographical position, cultural geographical aspects of one of the districts of Kohna and navqiran of Navoi region, the emergence of the first rural settlements, the area of Navbahor district ancient residential and cultural foci, research works on the history of the District, Historical and archaeological monuments in the district, pictures of the disappeared nabotot world, rockeries in Sarmysoy Gorge and its surroundings, arabtepa archaeological monument, natural and economic geographical aspects of the district.
Keywords: geographical location; archaeological monuments; protected areas; material cultural heritage; nabotot world; early settlement sites; nomadic herders; cultural geographical aspects